Collaborative Governance in the Management of Transportation Modes in DKI Jakarta Province - Isnawa Adji; I Nyoman Sumaryadi; Djohermansyah Djohan; Hyronimus Rowa (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
The research emphasizes the pivotal role of effective communication and stakeholder engagement in the success of collaborative governance, achieved through regular dialogues and consultations among all parties. This inclusive approach promotes cooperation and a sense of ownership among stakeholders, enhancing strategy effectiveness. Transparency and accountability are identified as key components in building trust among stakeholders and the public, contributing to a responsive transportation management system. Despite challenges, collaborative governance yields integrated transportation planning, improved traffic management, and enhanced public transportation services, aligning with sustainability goals. However, the study highlights the need for stronger leadership, robust conflict resolution mechanisms, and adaptability to evolving urban transportation dynamics for future enhancements and policy development.